Irene Dalis wedding reception photographs
Contact sheet of the Irene Dalis and George Loinaz wedding reception. Photographs include Irene's father, Peter Nicholas Dalis, giving a toast, the wedding guests and wedding party sitting down at the reception table, and candid shots of the bride and groom visiting with their guests.